107k views
5 votes
-6,-5,-4,-3,...rule
What is answer ​

User Ryan Epp
by
5.3k points

1 Answer

5 votes

Answer:


a_(n) = n - 7

Explanation:

There is a common difference between consecutive terms in the sequence

d = - 5 - (- 6) = - 4 - (- 5) = - 3 - (- 4) = 1

This indicates the sequence is arithmetic with nth term


a_(n) = a₁ + (n - 1)d

where a₁ is the first term and d the common difference

Here a₁ = - 6 and d = 1 , then


a_(n) = - 6 + 1 (n - 1) = - 6 + n - 1 = n - 7

User Derek Joseph Olson
by
5.2k points